Natural co-occurrence of multi-mycotoxins in unprocessed wheat grains from China. (December 2021) - Zhao, Jianyun; Cheng, Tianxiao; Xu, Wenjing; Han, Xiaomin; Zhang, Jing; Zhang, Hongyuan; Wang, Chong; Fanning, Séamus; Li, Fengqin
Abstract: This study aimed at assessing the occurrence of twelve mycotoxins, including deoxynivalenol (DON) and its derivatives, 3- and 15-acetyl-deoxynivalenol (3-ADON and 15-ADON), nivalenol (NIV), zearalenone (ZEN), fumonisins (FB1, FB2 and FB3 ) and aflatoxins (AFB1, AFB2, AFG1 and AFG2 ) in 338 unprocessed wheat samples harvested in 2018 from China by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). DON was found to be the most predominant and abundant mycotoxins followed by 3-ADON, 15-ADON, NIV, FB1, ZEN, FB3, FB2, AFB1, AFB2, AFG2 and AFG1 . Samples from Hubei and Anhui provinces that situated the Yangtze River recorded a higher positive rate for Fusarium mycotoxins. The positive rate and average concentration of fumonisins in wheat samples are relatively low while the co-occurrence of fumonisins as well as DONs and its derivatives 3-ADON and 15-ADON, ZEN and/or NIV was found to be 37.6%. Moreover, compared with wheat samples in 2017, the combined levels of DON and its derivatives, 3-ADON and 15-ADON in wheat samples harvested in the year of 2018 is higher with the incidence of co-occurrence of DON + 3-ADON + 15-ADON significantly raised which may due to the increased precipitation weather conditions. These findings suggest the necessity of monitoring contamination of Fusarium mycotoxins and further raise concerns as to DON + 3-ADON + 15-ADON co-occurrence in wheat in China in order to protect consumers' health from the toxins exposure risks. Highlights: Twelve mycotoxins are detected in 338 wheat samples harvested in 2018 from China. Deoxynivalenol (DON) is the most abundant toxin detected in wheat samples. The incidence of co-occurrence of DON, 3-ADON and 15-ADON in 2018 is raised. The incidence of co-occurrence of fumonisins with other Fusarium toxins is 37.6%.